Indonesian ESL Teachers’ Pedagogical Content Knowledge (PCK) in Responding to the Curriculum Changing - Bita Dwi Rahmani; Herri Mulyono; Ratih Novitasari (Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
This research is focused on the analyzing and mapping the pedagogical and content knowledge (PCK) of In-Service English High-School teachers in Indonesia in responding the Indonesian Curriculum Changing namely Curriculum 2013. This study was also conducted since the score of Teacher Competencies Test (UKG) for Indonesian ESL teacher was still low. Therefore, the questionnaire was designed and adapted from TPACK questionnaire to gather the data of Indonesian ESL Senior High School Teacher on their perception and understanding on Pedagogical Knowledge (PK), Content Knowledge (CK), Pedagogical and Content Knowledge (PCK) and also their understanding on Curriculum changing (CC) that happened recently. The data showed that the result of the teacher’s Pedagogical Knowledge (PK) and Content Knowledge (CK) were quite high with the score 50% which means that the teacher thought that they were quite competence on both knowledge. Meanwhile, there were more than 60% teachers believed that they were highly competence in implementing Pedagogical and Content Knowledge (PCK) on their teaching practice. However, in term of responding the curriculum change, most of the teachers gave the response as a quite competence rather than highly competence on the issue of curriculum changing. In short, this research shows the teacher’s perception of their own knowledge that they had in responding on Pedagogical Content Knowledge also the new curriculum knowledge. Therefore, this research is expected to be as another supporting evidence to confirm and mapping the teacher’s competences which is not only relying on the result of teacher competencies test/UKG.